SISTEM MONITORING KWH METER DIGITAL BERBASIS IOT PADA LABORATORIUM PERALATAN MEDIS - Widyawarman, Danang; Hastono, Tri (JOURNAL ONLINE OF PHYSICS, 2023)
The educational process, which is supported by adequate laboratory facilities and infrastructure, will produce professional higher education tri-dharma outputs, both for students and lecturers. The Medical Equipment Laboratory is a place where experimental studies with various equipment and devices, analyses, and observations are carried out. The amount of electrical energy used by a university can be measured using an electric energy meter, namely the kWh meter, but the university cannot monitor which building or room uses the most electrical energy because it only knows the amount of power used each month. Given these problems, a digital kWh Meter monitoring tool based on the Internet of Things (IoT) is designed to measure the amount of current, voltage, power, and costs that must be incurred while using medical equipment and can then be monitored in real time using the Blynk application as the server. The implementation system for monitoring the kwh meter using the PZEM-004T sensor has a very good accuracy rate of 99.52% for measuring voltage and 99.87% for measuring current on medical equipment in the medical equipment laboratory at the PGRI Yogyakarta University. It was found that the greater the applied load value, the more the impact on data outputs such as current and voltage would affect the size of the monthly electricity bill. The monitoring system can be carried out within a radius of 20 meters as long as the smartphone is connected to a WiFi connection. Monitoring activities and electrical device control activities can be carried out.